Metals in mussels from Italian mollusc culture plants (International Journal of Health, Animal Science and Food Safety, 2017)
The beneficial effects on human health of seafood are well known. However, seafood is a major source of exposition for consumers of most of the contaminants due to human activities such as breeding, industries, mining and agriculture: the overall level in biota, therefore seafood and particularly molluscs, dramatically increased over this last two centuries. This study evaluates the presence of Lead, Mercury, Cadmium, Arsenic, Nickel and Chromium in mussels from the Italian mussel culture plants, and estimate the risk that Italian consumer undergoes eating these molluscs. Mussels where collected at the wholesale fish market of Milan, the most important wholesale Italian fish market. The molluscs belonged to the   37 FAO marine area (corresponding to Mediterranean Sea), particularly from FAO 37.2.1 Ligury, 37.2.2. North Adriatic, middle Adriatic, Puglia, 37.2.3 Lazio and Sardinia, and were collected from July 2016 to February 2017. (FIG1). Analyses were carried out through inductively coupled plasma-mass spectrometry (ICP-MS) according to the Environmental Protection Agency (EPA) 3050B method. The sample concentrations were below the Maximum Levels (ML) given by Commission Regulation (EC) No 1881/2006 for Cadmium, Lead and Mercury, except one sample from south Adriatic sea, that showed Mercury concentration of 0.528 mg kg-1. Arsenic, Nickel and Chromium ML are not stated by EU. Arsenic concentration ranged from 2.05 to 13.35 mg kg-1, with the highest values found in Italian molluscs, Nickel concentration ranged from 0.00 to 3.98 mg kg-1. Chromium was found only in 5 of 30 sample analysed with a maximum concentration of 0.590 g kg-1. The tolerable intakes recommended by EFSA and on EU maximum levels, indicate that Italian mussels do not pose a risk consumers.
Keywords: Metals; ICP-MS; Mussels; Maximum Levels; Tolerable intakes.